Late flowering time enhances insect pollination of turnip rape. Issue 5 (22nd February 2019) - Toivonen, Marjaana; Herzon, Irina; Rajanen, Hanne; Toikkanen, Jenni; Kuussaari, Mikko
Abstract: Ecological intensification has been proposed as a strategy to mitigate the impacts of conventional intensive land use on pollinators and insect pollination. However, research has concentrated on the effects of land management on pollinator abundance and diversity, while studies directly measuring pollination services are still lacking for many crops and regions. This study examines the effects of landscape heterogeneity, pesticide use intensity and flowering time on insect pollination of turnip rape Brassica rapa ssp. oleifera, a major oil crop at high latitudes. The field experiment included monitoring pollinator visits on turnip rape flowers and measuring yield in 34 spring‐sown turnip rape fields in Southern Finland. The fields were situated in two landscape types that differed in the cover of arable land and represented independent gradients of pesticide use intensity and flowering time. Based on flower visits and number of seeds per silique, turnip rape was best pollinated in fields with late flowering time. The result suggests a temporal mismatch between crop flowering and the availability of pollination service in early sown fields. The increase in flower visits during summer was steeper among fields with low than high pesticide use, possibly due to a faster colony growth of important bee pollinators. Pollinator community in turnip rape fields was more diverse in heterogeneous landscapes with less arable land than in homogeneous field‐dominated landscapes, suggesting higher stability of pollination services in diverse landscapes. Total yield per plant was positively related to pesticide use intensity. The relationship between insect pollination and total yield was weakened by high compensation capacity of turnip rape, the plants producing more flowers under poor pollination. Synthesis and applications . Crop pollination can be enhanced by shifting sowing time to better match crop flowering to the peak availability of the most important pollinators. Reduced pesticide use may also enhance pollination services but can lead to the total yield reduction due to pests. This highlights the need for pollinator‐friendly pest control methods to maintain turnip rape yields while conserving pollination services. Abstract : Crop pollination can be enhanced by shifting sowing time to better match crop flowering to the peak availability of the most important pollinators. Reduced pesticide use may also enhance pollination services but can lead to the total yield reduction due to pests. This highlights the need for pollinator‐friendly pest control methods to maintain turnip rape yields while conserving pollination services. Foreign Language AbstractTiivistelmä: Maatalouden ekologista tehostamista on esitetty strategiaksi, jonka avulla intensiivisen maankäytön kielteisiä vaikutuksia pölyttäjiin ja hyönteispölytykseen voidaan hillitä. Tutkimukset maankäytön vaikutuksista viljelykasvien hyönteispölytykseen kuitenkin puuttuvat yhä monilta viljelykasveilta ja alueilta. Tämä tutkimus tarkasteli maiseman monimuotoisuuden, torjunta‐aineiden käytön ja kukinta‐ajan vaikutusta rypsin hyönteispölytykseen. Peltokokeessa seurattiin pölyttäjien vierailuja rypsin kukilla ja mitattiin satoa 34 kevätrypsipellolla Uudellamaalla. Pellot sijaitsivat kahdessa maisematyypissä, joista toinen oli peltovaltainen ja toinen monimuotoisempi ja vähemmän peltoa sisältävä. Lisäksi pellot erosivat toisistaan torjunta‐aineiden käytön ja kukinta‐ajan suhteen. Pölyttäjien kukkavierailut ja siementen määrä per litu olivat korkeimmillaan myöhään kukkineilla rypsipelloilla, mikä kertoo hyvästä pölytyksestä. Tuloksen perusteella aikaisin kylvetyt rypsipellot saattavat kukkia liian aikaisin pölyttäjien saatavuuden näkökulmasta. Voimakkaimmin pölyttäjien määrä lisääntyi kesän aikana niiden peltojen joukossa, joilla ei käytetty torjunta‐aineita. Mahdollinen selitys on, että tarhamehiläisten ja kimalaisten yhdyskunnat kasvoivat nopeimmin näiden peltojen läheisyydessä. Pölyttäjien monimuotoisuus oli suurempi monimuotoisessa kuin peltovaltaisessa maisemassa, mikä parantaa pölytyspalvelun vakautta muuttuvissa olosuhteissa. Kokonaissato per kasvi nousi torjunta‐aineiden käytön lisääntyessä. Hyönteispölytyksen ja sadon välistä yhteyttä heikensi rypsin hyvä kompensaatiokyky, jonka ansiosta heikosti pölyttyneet kasvit tuottivat enemmän kukkia. Yhteenveto ja sovellukset . Viljelykasvin pölytystä voi parantaa säätämällä kylvöaikaa siten, että kasvin kukinta ajoittuu tärkeimpien pölyttäjien runsaushuippuun. Torjunta‐aineiden käytön vähentäminen voi parantaa pölytystä mutta laskea samaan aikaan satoa tuholaisten ja rikkakasvien lisääntymisen takia. Pölyttäjäystävällisten kasvinsuojelukeinojen kehittäminen on tärkeää korkeiden rypsisatojen ja pölytyspalveluiden säilymisen kannalta.